A mobile robot based sensing approach for assessing spatial inconsistencies of a logistic system. (April 2017) - Arrais, Rafael; Oliveira, Miguel; Toscano, César; Veiga, Germano
Abstract : Highlights: A continuously monitoring of the consistency of a logistic supermarket is proposed. The spatial inconsistency detection increases the accuracy of the model. The logistic world model enables robots to perform in an effective way. A service-oriented approach was used to design and implement the logistic system. Results show that spatial inconsistencies detection is reliable and instant. Abstract: This paper demonstrates the potential benefits of the integration of robot based sensing and Enterprise Information Systems extended with information about the geometric location and volumetric information of the parts contained in logistic supermarkets. The comparison of this extended world model with hierarchical spatial representations produced by a fleet of robots traversing the logistic supermarket corridors enables the continuous assessment of inconsistencies between reality, i.e., the spatial representations collected from online 3D data, and the modelled information, i.e., the world model. Results show that it is possible to detect inconsistencies reliably and in real time. The proposed approach contributes to the development of more robust and effective Enterprise Information Systems.